Lessons Learned from a Near-Symmetrical North‒South Student Exchange/ International Service-Learning University Partnership - Robinson, Andrew; Ame, Robert; Dzisah, James; Wilson-Forsberg, Stacey (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
This article reports on an interview-based assessment of the 8-year experience of a North‒South university partnership between a Canadian university and three universities in a Sub-Saharan African country. The partnership concerned an atypical student exchange program whereby Southern graduate students travelled North to study while Northern undergraduates travelled South to perform international service-learning internships. The article asks if the partnership demonstrates the characteristics of a near-symmetrical partnership and why or why not. After explaining why the partnership appears to be near-symmetrical, the article identifies four factors that appear to have contributed to this near-symmetrical status (the atypical nature of the exchange program; thick ties between a small number of key actors, including a boundary spanner; inclusion of self-confident Southern partners; and positive effects of funder regulations) and suggests how these factors contributed to greater partnership balance. The conclusion presents recommendations for funders and university partners.